O psicólogo com atuação em emergência: experiência e significado - Cogo, Adriana Silveira (2010)
The psychology of emergencies and disasters is presented as a new playing field for the psychologist, as a logical consequence of various studies and experiments showing that events of this magnitude not only cause loss of lives, endanger the physical integrity of people, causing damage and economic losses, but also cause a profound emotional impact on individuals, communities, first responders and other professionals such as psychologists. In this study, therefore, from a case study, it was the experience and meaning of work in emergency psychologist with extensive work in the area and performance of psychological care in different situations. One can understand how, in terms of training, performance in this area, highlight your experience and also know the route to performance and professional training. Demonstrated the need for grounding and depth on issues relevant to disaster and emergencies, such as trauma, grief, posttraumatic stress disorder for which the trader can act with the necessary security and do a quality job